Pengembangan Pertanian Organik dan Pengurangan Stunting Desa Cikurubuk, Sumedang, Jawa Barat - Fahreza, Mohammad; Firdaus, Evan (LPPM Universitas Koperasi Indonesia, 2025)
The 2024 Community Service Program (PKM) in Cikurubuk Village, Sumedang Regency, was initiated to enhance the well-being of the community by promoting organic farming and combating stunting. This initiative spanned four months, from September 2023 to January 2024, with a focus on three key areas: (1) the advancement of organic farming, (2) the empowerment of the community in nutritional enhancement, and (3) the promotion of the village's primary products. The outcomes of the program demonstrated a noteworthy rise in the number of farmers shifting towards organic agriculture, leading to a growth in organic farmland from 5 hectares to 20 hectares. Furthermore, organic rice production surged from 20 tons to 50 tons per harvest. Through a series of health education sessions, the distribution of supplementary food, and the monitoring of child growth and development, the program effectively decreased the stunting rate in Cikurubuk Village from 30% to 20%. Additionally, the implementation of the Budikdamber project, which revolves around aquaponics-based fish and vegetable farming, significantly bolstered household food security. The formulation of marketing strategies for the village's signature products, including the Patani organic rice, made substantial headway through digital platform promotions and local bazaars. All in all, this endeavor had a positive impact on the economic and health status of the Cikurubuk Village residents.